ANALISIS EFISIENSI DAN EFEKTIVITAS PROSES PERENCANAAN DAN PENGANGGARAN DAERAH - Sopanah Sopanah (The Indonesian Accounting Review, 2011)
The purpose of this research is to describe the process consistency and the result of planning and budgeting in Malang City. Besides that it also formulates the recommendation for increasing participative effectiveness and planning process eficiency, budgeting and transparenq). Based on the document of development planning which has been elaborated earlier and the result of survey and inferential researcher analysis, i, appears that there are sotne inconsistencies in planning process and budgeting in the area of Malang City. Budgeting planning process of the area are said to be effective when all are related to the specified program priority, the intention can be reached in timely mean and matched with regulation. Based on the result of survey to 50 respondents, they said that inconsistencies have occurred. These are due to the goods that are not totally related to the regulation (product punished). It is also due to the time of doing the budgeting process. From 6 steps in budgeting planning process, they are in consistency. It is found that budgeting planning process in Malang City is not yet effective. Meanwhile, budgeting planning process of the area are said to be eficient if some of the proposals from Musrenbang (the conformity of planning and developrnent) are accommodated in APBD. It can be generalized that very few proposals are agreed due to the limited budget.